The competitiveness of young professionals on the labour market: the criteria and factors - A. G. Nikulin (Путеводитель предпринимателя)
Presents criteria and factors shaping the competitiveness of young professionals on the labour market. The urgency of work is explained by the necessity to increase the competitiveness of young specialists for their employment.